2014
DOI: 10.1037/a0036521
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile justice girls’ depressive symptoms and suicidal ideation 9 years after multidimensional treatment foster care.

Abstract: Objective Multidimensional Treatment Foster Care (MTFC) has been found to reduce delinquency among girls in juvenile justice through 2-year follow-up. Given that such girls are at elevated risk for suicide and depression into adulthood, we tested MTFC effects on long term trajectories of suicidal ideation and depressive symptoms. Method Girls [n =166; mean (SD) age = 15.3 (1.2) years; 68 % Caucasian] with a recent criminal referral who were mandated to out-of-home care were enrolled in two sequential cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…Moreover, the GMA effect size is independent of the intercorrelations among the repeated measures over time, which meta-analysts have shown to be an important criterion for the d from classical analysis of repeated-measures data to be expressed in the same metric as the d calculated from independent (completely randomized) groups designs (Becker, 1988; Dunlap, Cortina, Vaslow, & Burke, 1996; Morris, 2008; Morris & DeShon, 2002). The GMA d , as calculated with Equation 1, is now frequently found in studies of intervention efficacy, particularly in JCCP (e.g., Aderka, Gillihan, McLean, & Foa, 2013; Arch, Eifert, Davies, Vilardaga, Rose, & Craske, 2012; Chaffin, Funderburk, Bard, Valle, & Gurwitch, 2011; Kerr, DeGarmo, Leve, & Chamberlain, 2014; Ljótsson et al, 2013; Safren, O'Cleirigh, Bullis, Otto, Stein, & Pollack, 2012; Twohig, Hayes, Plumb, Pruitt, Collins, Hazlett-Stevens, & Woidneck, 2010). …”
Section: Standardized Effect Sizes For Multilevel and Latent Growth Mmentioning
confidence: 99%
“…Moreover, the GMA effect size is independent of the intercorrelations among the repeated measures over time, which meta-analysts have shown to be an important criterion for the d from classical analysis of repeated-measures data to be expressed in the same metric as the d calculated from independent (completely randomized) groups designs (Becker, 1988; Dunlap, Cortina, Vaslow, & Burke, 1996; Morris, 2008; Morris & DeShon, 2002). The GMA d , as calculated with Equation 1, is now frequently found in studies of intervention efficacy, particularly in JCCP (e.g., Aderka, Gillihan, McLean, & Foa, 2013; Arch, Eifert, Davies, Vilardaga, Rose, & Craske, 2012; Chaffin, Funderburk, Bard, Valle, & Gurwitch, 2011; Kerr, DeGarmo, Leve, & Chamberlain, 2014; Ljótsson et al, 2013; Safren, O'Cleirigh, Bullis, Otto, Stein, & Pollack, 2012; Twohig, Hayes, Plumb, Pruitt, Collins, Hazlett-Stevens, & Woidneck, 2010). …”
Section: Standardized Effect Sizes For Multilevel and Latent Growth Mmentioning
confidence: 99%
“…MTFC utilizes specialized foster homes where caregivers are trained to manage delinquent behaviors until youth can transition back to their families. MTFC also provides individual and family therapy, educational programming, and psychiatric care and is effective in reducing delinquent behaviors, justice system contacts, substance use, depression, and teen pregnancy (Chamberlain, Leve, & DeGarmo, 2007; Kerr, DeGarmo, Leve, & Chamberlain, 2014; Smith, Chamberlain, & Eddy, 2010). Though only evaluated with adolescents, MTFC may prove to be useful if adapted for transition age youth, especially given the push to extend foster care services through the transition age and the focus of MTFC on transitioning youth from foster care back to their communities.…”
Section: Evidence-based and Promising Practices And Policiesmentioning
confidence: 99%
“…Despite these challenges several prevention programs that target child or contextual risk and protective factors have found long-term effects on suicidal behavior. Kerr, DeGarmo, Leve and Chamberlain (2014) found that a parenting focused intervention for girls in foster care reduced suicidal ideation (i.e. thoughts about suicide).…”
mentioning
confidence: 99%